Identification and Optimization of the Algicidal Activity of a Novel Marine Bacterium Against Akashiwo sanguinea - Li, Shuangfei; Wang, Shilin; Xie, Linshen; Liu, Yan; Chen, Huirong; Feng, Jie; Ouyang, Liao (Frontiers in Marine Science, 2022)
Akashiwo sanguinea is a marine algal species associated with harmful algal blooms (HABs). We found that Vibrio brasiliensis H115, isolated from the seawater of Dameisha Bay (Shenzhen), China, can lyse A. sanguinea. At bacteria-to-algae cell ratios of 7,000:1 and 8,000:1, 73.9 ± 1.8 and 81.4 ± 2.8%, respectively, of A. sanguinea were lysed in just 10 min. V. brasiliensis H115 attacks A. sanguinea by secreting extracellular active compounds. Single-factor experiments showed that the optimum growth conditions for strain H115 were medium 2216E with extra sorbitol (1.0%) and peptone (2.0%), pH 7.5, a shaking speed of 200 rpm, and incubated at 40°C for 54 h. Under these optimized conditions, the algicidal efficiency of strain H115 against A. sanguinea improved by 69.4%. Large biomasses were obtained when strain H115 was incubated in 5- and 100-L bioreactors, with algicidal efficiencies against A. sanguinea reaching 94.2 ± 0.5 and 97.1 ± 0.6%, respectively, in 4 h of co-incubation. These results suggest that strain H115 and its active algicidal compounds may be viable for controlling the outbreaks of A. sanguinea.